The Application of Accounting for Medicines Inventory Based on PSAP. 05 at Regional Public Hospital - Nurul Latifah Nurdin; Haliah; Nirwana (Yayasan Ilomata, 2023)
This study aims to analyze the application of inventory accounting to the applicable standard which are applied by the object of Regional Public Hospital. The applicable standard referred to in this study is the Statement of Government Accounting Standards Number 05 concerning inventory accounting, which is contained in Government Regulation Number 71 of 2010. The hospital which is the object of this research is RSUD Prov. Jawa Timur. This Study uses a quantitative data analysis method and a literature study approach. Sources of data use secondary data in the form performance report BLUD of the official hospital website. The result of this study indicates that the application of the Medicines Inventory Accounting at Regional Public Hospital has been applied in accordance with the government Accounting Standards Statement (PSAP) Number 05.